If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = -2(x + 5) Reorder the terms: -12 = -2(5 + x) -12 = (5 * -2 + x * -2) -12 = (-10 + -2x) Solving -12 = -10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12 + 2x = -10 + -2x + 2x Combine like terms: -2x + 2x = 0 -12 + 2x = -10 + 0 -12 + 2x = -10 Add '12' to each side of the equation. -12 + 12 + 2x = -10 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = -10 + 12 2x = -10 + 12 Combine like terms: -10 + 12 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| In(2x)=-2 | | 4-7x+6x=0 | | t=(x-7)(2+y) | | 9m=6(a+4) | | -19=2+4(h+7) | | 754/1000000 | | 3x(2x-3)=27 | | 17j-6=14j+7 | | 18.24=-16t^2+24t+8 | | 3n-9=2n+13 | | 8-6n=-7+5(5n+3) | | 7i/8i | | -8x+y=50 | | x-12/5=-6 | | 7-(2-y)=-4 | | 18.24=-16t+24t+8 | | x+39-3x-40=949 | | 9*45=5(f-32) | | (n-12)*8=80 | | x+x+37+4x-40=819 | | 19-5x=7x+19 | | -3y-27=-6(y+6) | | t=(x+y)(2x-y) | | 5*(x-2)=2+2x+x+4 | | 0=5x^2+15 | | 7x-32+3x+12=180 | | -24x=7x-4 | | (n-8)*8=32 | | 10y+8x=210 | | (j+9)(5j+7)=0 | | x^2-15x+68=0 | | 9(2+r)-3(r-1)=33 |